A Revision of the Selenocosmiine Tarantula Genus Phlogiellus Pocock 1897 (Araneae: Theraphosidae), with Description of 4 New Species - Steven C. Nunn; Rick C. West; Volker Von Wirth (International Journal of Zoology)
The tarantula genus Phlogiellus (Pocock 1897) is revised. The genus is diagnosed against all other selenocosmiine genera for the first time along with a new generic description. The tribe Yamiini (Kishida 1920) is diagnosed against all other selenocosmiine tribes. All Phlogiellus species are diagnosed from all congeners; all species are mapped. Complete dichotomous keys for both sexes of all species are included. Where appropriate, intraspecific variation is discussed. Four new species are described: P. bogadeki sp. nov. from Hong Kong, P. johnreylazoi sp. nov. from Palawan Island, Philippines, P. moniqueverdezae sp. nov. from Ranong, Thailand, and P. pelidnus sp. nov. from Sabah, Borneo. The type species P. atriceps (Pocock 1897) holotype male is redescribed and the male P. baeri (Simon 1877) is described in detail for the first time. The validity of P. inermis (Ausserer 1871) is confirmed. Relationships between all known selenocosmiine genera and Phlogiellus from the Philippines are discussed and several character traits are newly diagnosed. The tribe Phlogiellini (West et al. 2012) is a junior synonym of Yamiini (Kishida 1920). Selenocosmia orophila (Thorell 1897) from Myanmar, Selenocosmia insulana (Hirst 1909) from Djampea (= Jampea) Island, and Selenocosmia obscura (Hirst 1909) from Sarawak, Borneo, are transferred to Phlogiellus, altering the specific names to Phlogiellus orophilus (Thorell 1897) comb. nov., Phlogiellus insulanus (Hirst 1909) comb. nov., and Phlogiellus obscurus (Hirst 1909) comb. nov. Phlogiellus subarmatus (Thorell 1891) is transferred to Chilobrachys (Karsch 1891), becoming Chilobrachys subarmatus (Thorell 1891) comb. nov. Phlogiellus kwebaburdeos (Barrion-Dupo et al., 2014) is transferred to Orphnaecus (Simon 1892), becoming Orphnaecus kwebaburdeos (Barrion-Dupo et al., 2014) comb. nov. Phlogiellus ornatus (Thorell 1897) and Phlogiellus nebulosus (Rainbow 1899) are considered species inquirenda. Phlogiellus baeri (Simon 1877) is no longer considered incertae sedis; Phlogiellus bicolor (Strand 1911) and Phlogiellus insularis (Simon 1877) are considered incertae sedis.